The helm of midnight - Lostetter, Marina J. (Five penalties, 2021)
"A legendary serial killer stalks the streets of a fantastical city in The Helm of Midnight, the stunning first novel in a new trilogy from acclaimed author Marina Lostetter. In a daring and deadly heist, thieves have made away with an artifact of terrible power-the death mask of Louis Charbon. Made by a master craftsman, it is imbued with the spirit of a monster from history, a serial murderer who terrorized the city. Now Charbon is loose once more, killing from beyond the grave. But these murders are different from before, not simply random but the work of a deliberate mind probing for answers to a sinister question. It is up to Krona Hirvath and her fellow Regulators to enter the mind of madness to stop this insatiable killer while facing the terrible truths left in his wake"--